Lingkar lengan atas, indeks massa tubuh, dan tinggi fundus ibu hamil sebagai prediktor berat badan lahir - Weni Kurdanti; Tri Mei Khasana; Lastmi Wayansari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Upper arm circumference, body mass index, and fundal height of pregnant women to estimate birth weightBackground: Accuracy of estimated infant’s birth weight is one of the most important measurements at the beginning of labor. Some anthropometric measures of pregnant women are upper arm circumference (MUAC) as a screening tool for chronic energy deficiency, body mass index (BMI) for assessment of chronic energy deficiency status, and indicators of fundal height to estimate birth weight. However, many studies with varying results are related to the accuracy of estimated birth weight.Objective: The study aimed to compare the capacity of MUAC, BMI, and fundal height indicators in predicting birth weight.Methods: The type of research is a cross-sectional study carried out at the Sadewa Maternal and Child Hospital in Yogyakarta in June-August 2018 with a 376 sample. The independent variables were MUAC, BMI, and fundal height, and the dependent variable is birth weight. Bivariate analysis using Pearson correlation and AUC and ROC curve tests.Results: There is a relationship between BMI and the fundal height of pregnant women with birth weight. The AUC BMI value (AUC=0.519) was found to be the highest compared to the MUAC (AUC=0.496) and fundal height (AUC=0.466) measurements.Conclusions: Pre-pregnancy BMI had a better capacity for predicting birth weight than MUAC and fundal height.